Prognostic effect of high-flux hemodialysis in patients with chronic kidney disease - Li,X. (2016)
We investigated the prognostic effects of high-flux hemodialysis (HFHD) and low-flux hemodialysis (LFHD) in patients with chronic kidney disease (CKD). Both an electronic and a manual search were performed based on our rigorous inclusion and exclusion criteria to retrieve high-quality, relevant clinical studies from various scientific literature databases. Comprehensive meta-analysis 2.0 (CMA 2.0) was used for the quantitative analysis. We initially retrieved 227 studies from the database search. Following a multi-step screening process, eight high-quality studies were selected for our meta-analysis. These eight studies included 4967 patients with CKD (2416 patients in the HFHD group, 2551 patients in the LFHD group). The results of our meta-analysis showed that the all-cause death rate in the HFHD group was significantly lower than that in the LFHD group (OR=0.704, 95%CI=0.533-0.929, P=0.013). Additionally, the cardiovascular death rate in the HFHD group was significantly lower than that in the LFHD group (OR=0.731, 95%CI=0.616-0.866, P<0.001). The results of this meta-analysis clearly showed that HFHD decreases all-cause death and cardiovascular death rates in patients with CKD and that HFHD can therefore be implemented as one of the first therapy choices for CKD.